Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00894-014-2492-1
|View full text |Cite
|
Sign up to set email alerts
|

Introducing “UCA-FUKUI” software: reactivity-index calculations

Abstract: A new software (UCA-FUKUI) has been developed to facilitate the theoretical study of chemical reactivity. This program can calculate global parameters like hardness, softness, philicities, and Fukui condensed functions, and also local parameters from the condensed functions. To facilitate access to the program we have developed a very easy-to-use interface. We have tested the performance of the software by calculating the global and local reactivity indexes of a group of representative molecules. Finite differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(53 citation statements)
references
References 78 publications
1
49
0
2
Order By: Relevance
“…Partial charges based on the atomic polar tensor distribution of PUCorr‐1 (Table ) shows that the most favorable sites of interactions between the inhibitor and the metal atoms are the nitrogen and oxygen atoms of the urea linkage (N‐16, N‐18, N‐50, O‐52, O‐53, and N‐54). In addition, Fukui indices which constitute local descriptors useful in the rationalization of the reactivity of molecules according to the HSAB principle showed that the most prominent sites for nucleophilic ( f + ) and electrophilic ( f − ) attacks are distributed mainly across the aromatic system and the heteroatoms in PUCorr‐1, indicating the likelihood of the polymer to undergo stronger adsorption with the metal atoms in agreement with other experimental results.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Partial charges based on the atomic polar tensor distribution of PUCorr‐1 (Table ) shows that the most favorable sites of interactions between the inhibitor and the metal atoms are the nitrogen and oxygen atoms of the urea linkage (N‐16, N‐18, N‐50, O‐52, O‐53, and N‐54). In addition, Fukui indices which constitute local descriptors useful in the rationalization of the reactivity of molecules according to the HSAB principle showed that the most prominent sites for nucleophilic ( f + ) and electrophilic ( f − ) attacks are distributed mainly across the aromatic system and the heteroatoms in PUCorr‐1, indicating the likelihood of the polymer to undergo stronger adsorption with the metal atoms in agreement with other experimental results.…”
Section: Resultssupporting
confidence: 85%
“…Reactivity descriptors such as global hardness ( η ), electron affinity ( A ), ionization potential ( I ), electronegativity ( χ ), and fractions of transferred electrons (Δ N ) were computed according to the DFT‐Koopman's theorem . To check possible local reactivity sites on the molecules, condensed Fukui functions were calculated using the UCA‐FUKUI v.1.0 software via the finite difference approximation method, which provides a good correlation with the frontier molecular orbital method …”
Section: Methodsmentioning
confidence: 99%
“…All calculations were performed out in the Gaussian 09 package . The Fukui functions were extracted with the program UCA‐FUKUI, the NCI regions were calculated using the NCI Plot program and the electrostatic potential (ESP) surface was constructed with the help of Molden 5.2 …”
Section: Methodsmentioning
confidence: 99%
“…Las medidas de EC 50 muestran que el vinil-acrilato (16) es el más reactivo de los compuestos de la serie 6 (Figura 7), seguido consecutivamente por el vinil-crotonato (17) y etil-crotonato (18 …”
Section: Serieunclassified
“…16,17 No obstante, la reactividad de sistemas moleculares complejos no puede ser racionalizada solo mediante este parámetro, dando lugar a la necesidad de considerar otros descriptores de reactividad. 18 Atendiendo a esto, han surgido conceptos derivados tales como el índice de electrofilicidad, 19 poder electrodonador y poder electroaceptador, 20,21 electrofugalidad y nucleofugalidad, 22,23 índice de nucleofilicidad, 24 entre otros. De los descriptores anteriormente mencionados, el índice de electrofilicidad w ha sido el más ampliamente utilizado en la literatura para reproducir y ayudar a entender el comportamiento electrofílico de múltiples sistemas moleculares, 3,[25][26][27] sin embargo, su definición podría carecer de rigor considerando el hecho de que fue construido a partir de un modelo donde la energía del sistema es considerada como una función continua y diferenciable con respecto al número de electrones, lo que implica que las respuestas de una especie química a los procesos de donación o aceptación de carga deberían ser iguales.…”
Section: Introductionunclassified